A Case Report on Steroid Induced Acneiform Eruptions - Jeyaraj, Kavipriya; Krishnakumar, Megha; Sivakumar, Velusamy; Venkatakrishnan, Leelakrishnan (Indian Journal of Pharmacy Practice)
Acne is the chronic inflammatory disease of the pilosebaceous unit, characterized by the formation of comedones, erythematous papules and pustules shortly after starting topical or oral corticosteroid. We report a case of acneiform eruptions on a Eosinophilic gastroenteritis (EGE) patient who was treated with prednisolone 30 mg 1-0-0, 2 weeks, three months ago. She developed pustular rashes over the face and back on and off during past 3 months. Presently she got admitted in the gastroenterology department for reoccurence of the symptoms associated with EGE and treated with prednisolone 30 mg 1-0-0. Dermatology opinion was sought for the aggravated pustular rashes over the face and back confirmed to be prednisolone induced acneiform eruptions. Following which, prednisolone was withdrawn within 48 h of admission and treated symptomatically with Clindamycin 1% gel.
Keywords: Eosinophilic gastroenteritis; acneiform eruptions; Prednisolone; Steroids; Pustular Rashes